2003
DOI: 10.1071/fp03078
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation for adventitious rooting in response to low phosphorus availability: potential utility for phosphorusacquisition from stratified soils

Abstract: We hypothesized that adventitious roots may improve crop adaptation to low-phosphorus soils by enhancing topsoil foraging. In a tropical field study, phosphorus stress stimulated adventitious rooting in two phosphorus-efficient genotypes of common bean (Phaseolus vulgaris L.) but not in two phosphorus-inefficient genotypes. Although phosphorus availability had no consistent effects on the length or biomass of whole root systems, it had differential effects on adventitious, basal, and taproots within root syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
145
0
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(165 citation statements)
references
References 44 publications
7
145
0
13
Order By: Relevance
“…The importance of root architectural traits in P acquisition has been investigated (Beebe et al, 2006;Liao et al, 2004;Miller et al, 2003). Miller et al (2003) reported that greater production of adventitious roots in common beans helps in P acquisition by improving plant foraging in the most P rich soil environment, while Beebe et al (2006) noted that basal root development and specific root length are responsible for efficient P acquisition.…”
Section: Response To P Deficiencymentioning
confidence: 99%
See 3 more Smart Citations
“…The importance of root architectural traits in P acquisition has been investigated (Beebe et al, 2006;Liao et al, 2004;Miller et al, 2003). Miller et al (2003) reported that greater production of adventitious roots in common beans helps in P acquisition by improving plant foraging in the most P rich soil environment, while Beebe et al (2006) noted that basal root development and specific root length are responsible for efficient P acquisition.…”
Section: Response To P Deficiencymentioning
confidence: 99%
“…Plant root architecture regulates the capacity of soil explored by roots, thereby playing a central role in P acquisition. Since P content and availability are more in top than in subsoil, root architectural traits that allow the exploration and use of P from surface layers govern P acquisition (Beebe et al, 2006;Liao et al, 2004;Miller et al, 2003). The P-efficient common bean genotypes which increase the below-ground biomass are able to acquire P in P-deficiency conditions (Liao et al, 2004;Namayanja, Semoka, Buruchara, Nchimbi, & Waswa, 2014).…”
Section: Response To P Deficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Quantifying the architecture of root systems is essential because crop productivity is almost always influenced by the availability and accessibility of water and nutrients that are heterogeneously distributed in the soil (Miller et al 2003;Cichy et al 2009;Gregory et al 2009). Root architecture directly impacts the capture of such soil resources and is, therefore, fundamental to crop productivity (Lynch 1995;Casson and Lindsey 2003;Malamy 2005;Watt et al 2006;Dunbabin 2007;Fita et al 2008;Gregory et al 2009).…”
Section: Introductionmentioning
confidence: 99%